2012
DOI: 10.4236/fns.2012.36106
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Eating Practices among Jordanians

Abstract: Culture has an enormous impact on individuals’ food choices and practices. This research aimed to screen cultural eating practices among Jordanians. Jordanian adults (N = 4750) completed a survey with regard to common eating practices in Jordan. Practices were classified into 4 themes, namely regular eating practices (7 practices), seasonal eating practices (4 practices), eating practices in social occasions (6 practices), and eating practices in religious occasions (10 practices). Interestingly, most nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Bawadi et al mentioned several healthy foods in Jordanian cuisine such as Bread dipped in olive oil and dried thyme, raw onion with dishes made of lentil [38]. Olive R.A. Habashneh et al oil has antimicrobial activity [39].…”
Section: Discussionmentioning
confidence: 98%
“…Bawadi et al mentioned several healthy foods in Jordanian cuisine such as Bread dipped in olive oil and dried thyme, raw onion with dishes made of lentil [38]. Olive R.A. Habashneh et al oil has antimicrobial activity [39].…”
Section: Discussionmentioning
confidence: 98%
“…Customs such as weddings, birth of a child, funerals, birthdays, and specific religious and national ceremonies call for serving of food. Bawadi and colleagues (2012) concluded that culture in Jordan has massive influences on eating practices and food choices, including influences that negatively affect good eating practices.…”
Section: Introductionmentioning
confidence: 99%
“…A sense of social obligation also forced hosts to serve food in excess to guests which added a social burden and pressure on patients to eat more food than was recommended. A previous study identified that when Jordanians invite guests to dinner, and as a sign of generosity, 93% (n=4423) of 5000 participants offer large portions, and 91% (n=4341) of the study participants keep insisting on people having more food (Bawadi et al, 2012). Public health campaigns can be utilized for raising public awareness of the social and emotional needs of people with diabetes, to improve their lives and those at risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%